Terbuthylazine, atrazine, and atrazine + mesotrione for weed control in second-crop maize in Brazil - Paiola Albrecht, Leandro; Junior Paiola Albrecht, Alfredo; Bottcher, Aderlan Ademir; Greguer de Carvalho, Matheus; Yamada Danilussi, Maikon Tiago; Moreira Silva, André Felipe; Larini, Willian Felipe; Tanaka Torigoe, Rafael (Revista Ceres, 2025)
Terbuthylazine, as well as atrazine, is a triazine with the mechanism of action of photosystem II (PSII) inhibitors, effective in controlling weeds in maize crops. The aim of this study was to assess the efficacy of terbuthylazine, atrazine, and atrazine + mesotrione, alone or in mixtures with glyphosate, in weed control for post-emergence application in maize. The experiment was conducted over two growing seasons, evaluating weed control, damage symptoms in maize and maize yield. No damage symptoms were observed in maize, and when differences in yield were observed, they were due to differences in treatment efficacy in weed control. The efficacy of terbuthylazine is akin to that of atrazine in controlling broadleaf weeds (until 93.8%) and tends to be superior in controlling grasses (until 87.5% for terbuthylazine, until 76.3% for atrazine) or Commelina benghalensis (until 91.3% for terbuthylazine, until 82.5% for atrazine). Terbuthylazine or atrazine + mesotrione, alone or in a mixture with glyphosate, were effective in post-emergence weed control in maize, with a broad spectrum of action. Atrazine, alone or in a mixture with glyphosate, was effective in controlling broadleaf weeds (Richardia brasiliensis, Bidens subalternans, and volunteer soybeans).